2022
DOI: 10.3390/cancers14184506
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atm Loss on Radiosensitivity of a Primary Mouse Model of Pten-Deleted Brainstem Glioma

Abstract: Diffuse midline gliomas arise in the brainstem and other midline brain structures and cause a large proportion of childhood brain tumor deaths. Radiation therapy is the most effective treatment option, but these tumors ultimately progress. Inhibition of the phosphoinositide-3-kinase (PI3K)-like kinase, ataxia–telangiectasia mutated (ATM), which orchestrates the cellular response to radiation-induced DNA damage, may enhance the efficacy of radiation therapy. Diffuse midline gliomas in the brainstem contain loss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A recent study identified ATM inhibition as a potent radiosensitization strategy in a variety of patient-derived pediatric high-grade glioma models 6 . We found that functional ATM loss radiosensitized primary mouse models of DMG driven by p53 loss, but not those that were p53 wildtype 5,11 . ATM loss increased tumor sensitivity to radiotherapy by radiosensitization of neoplastic cells rather than vasculature 12 .…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…A recent study identified ATM inhibition as a potent radiosensitization strategy in a variety of patient-derived pediatric high-grade glioma models 6 . We found that functional ATM loss radiosensitized primary mouse models of DMG driven by p53 loss, but not those that were p53 wildtype 5,11 . ATM loss increased tumor sensitivity to radiotherapy by radiosensitization of neoplastic cells rather than vasculature 12 .…”
Section: Introductionmentioning
confidence: 75%
“…Almost all p53-altered primary mouse models are radioresistant and are radiosensitized by Atm loss, including (i) a model driven by p53 loss with wild type H3f3a 5 , (ii) a model driven by both p53 loss and by loss of Ink4A/ARF 5 , and (iii) the H3.3K27M/TP53 mutant model reported here (Figure 2C). In contrast, Atm loss is unable to radiosensitize primary p53-wildtype brainstem glioma mouse models, including models driven by Ink4A/ARF loss 5 and models driven by Pten loss 11 . Of note, a recent study comprehensively profiled that pharmacologic ATM inhibition radiosensitized both p53-mutant and p53-wild type patient-derived models of DMG and pediatric high-grade glioma 6 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The analysis of only 10 glioma models limits our ability to comprehensively evaluate how the spectrum of genetic alterations influence treatment outcome. For example, PTEN deletion is common in GBM and was reported to limit the radiosensitizing effects of ATM deletion in a model of brainstem glioma ( 64 ). Likewise, the interplay between inherent radiation sensitivity and radiosensitizing effects of ATM inhibition needs to be explored.…”
Section: Discussionmentioning
confidence: 99%